(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
One of the indispensable resources of the human being is water, but there are few populations that have this element in the purest way. In the urban area of Quindío have been several studies of the quality on drinking water, but not in the rural area. Therefore, we evaluate the water condition consumed by the rural population; In this case, some BD BBLD Crystal lab tests were performed for the identification of bacteria and IFI technique for parasites where were found 9 species of bacteria in which the most frequent were Enterobacter cloacae y Klebsiella oxytoca, 11 genre of parasites belonging to helminths and protozoa, Opisthorchis sp, Strongyloides sp, Giardia sp and 7 genre of algae. In spite of the fact that the values of physicochemical parameters were into the established limits according to the normativity, these conditions are allowing the growth of microorganisms in the water; most of them are causing various gastrointestinal diseases in humans, and the presence of these organisms suggest us that the consumed water by the rural population in the municipality of Circasia is not suitable for human consumption since it is evident the presence of bacteria, helminths and protozoa, and it does not comply with the condition of quality on drinking water. Thus, since it does not have a permanent treatment, water must be boiled before it is consumed.